Computational and theoretical studies on ZnS[x]Se[1-x] (0≤x≤1) / Ghassan H. Esa Al-Shabeeb - Al-Shabeeb, Ghassan H. Esa (2012)
The aim of this work is to study a theory of the energy band gap of ZnSxSe1-x (0≤ x ≤1) materials, and to obtain the density of states (DOS) in a quantizing magnetic field. From k .p